Efficient inverted-structure polymer solar cells with reduced graphene oxide for anode modification - Kang, Tae-Woon; Noh, Yong-Jin; Kim, Seok-Soon; Joh, Han-Ik; Na, Seok-In (ELSEVIER SCIENCE INC, 2015)
Enhanced cell-efficiency of inverted bulk-heterojunction based polymer solar cells (PSCs) was achieved by anode modification with reduced graphene oxide (rGO). The rGO thin film was obtained with spin-coating of a cost-effective rGO solution dissolved in ethanol on top of the organic photoactive layer, and the effects of the rGOs as a new interlayer on device-performances of inverted-structure PSCs were investigated. The inverted PSC with r-GO showed a remarkable enhancement in power conversion efficiency compared with the cells with no interfacial layers. In particular, the inverted device with rGO showed highly comparable efficiencies and superior PSC-stability to conventional PEDOT:PSS-based inverted PSCs. (C) 2014 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.
Keywords: HIGHLY EFFICIENT; TRANSPORT LAYER; HOLE